2022
DOI: 10.1088/1674-1056/ac3990
|View full text |Cite
|
Sign up to set email alerts
|

Pressure tuning of the anomalous Hall effect in the kagome superconductor CsV3Sb5

Abstract: Controlling the anomalous Hall effect (AHE) inspires potential applications of quantum materials in the next generation of electronics. The recently discovered quasi-2D kagome superconductor CsV3Sb5 exhibits large AHE accompanying with the charge-density-wave (CDW) order which provides us an ideal platform to study the interplay among nontrivial band topology, CDW, and unconventional superconductivity. Here, we systematically investigated the pressure effect of the AHE in CsV3Sb5. Our high-pressure transport m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…It is in agreement with the reported observation that both the electron and phonon play a role in the formation of CDW [37]. Very recently, through the zerofield muon spin relaxation technique, an intrinsic local magnetic field was observed in the 2 × 2 CDW phase of CsV 3 Sb 5 [25]. However, no measurable local spin moments or magnetic correlations can be responsible for it.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is in agreement with the reported observation that both the electron and phonon play a role in the formation of CDW [37]. Very recently, through the zerofield muon spin relaxation technique, an intrinsic local magnetic field was observed in the 2 × 2 CDW phase of CsV 3 Sb 5 [25]. However, no measurable local spin moments or magnetic correlations can be responsible for it.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the 2 × 2 CDW shows a novel chirality, where the electron occupation exhibits an 'A-B-C-A-B-C' structure at the six vertices of the hexagonal cell, and the chirality is defined as the clockwise or anticlockwise direction from the minimum to maximum of electron occupations. Furthermore, the chirality can be modulated unusually by the magnetic field, which indicates that the time inversion symmetry of the system is broken [24][25][26]. In correlated electron systems, chirality usually occurs in static spin system or dynamic current system [27], while it is rare in static charge system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent high pressure experiments, it was shown that the suppression of CDW leads to the enhanced superconductivity upon increasing pressure and a second superconducting dome appears at even higher pressures [14,47,48,50,[53][54][55][56]. It will be interesting to establish precise relationship between the onset temperature of the anomalous Hall effect and superconductivity as well as CDW in pressurized systems.…”
Section: Discussionmentioning
confidence: 99%
“…In recent high pressure experiments, it was shown that the suppression of CDW leads to the enhanced superconductivity upon increasing pressure and a second superconducting dome appears at even higher pressures [14,50,51,53,[56][57][58][59]. It will be interesting to establish precise relationship between the onset temperature of the anomalous Hall effect and superconductivity as well as CDW in pressurized systems.…”
mentioning
confidence: 98%